Single‑dip colorimetric detection of cyanide using paper‑based analytic device based on immobilized silver nanoparticles - Budlayan, Marco Laurence M (Archīum Ateneo, 2022)
The need to monitor the presence of cyanide (CN−) in water is necessary to minimize the risks to aquatic ecosystems and human health. In this paper; a paper-based analytical device (PAD) was fabricated by immobilizing silver nanoparticles (AgNPs) on filter paper (FP) for the semi-quantitative colorimetric detection of CN− in water. The average diameter of the synthesized AgNPs was estimated to be around 26.23 ± 8.37 nm; with a characteristic optical absorption peak around 420 nm. Scanning electron microscopy and energy-dispersive X-ray spectroscopy results confirmed the successful immobilization of AgNPs on the filter paper via direct immersion technique. The potential of the fabricated FP-AgNPs PAD as a colorimetric sensor for CN− was evaluated using water samples contaminated with various ions and CN− concentration. Here; a color change from yellow to colorless was instantly observed as the FP-AgNPs PAD was exposed to water samples containing CN−. Interestingly; no color change was observed for samples exposed to other analytes suggesting the good selectivity of the FP-AgNPs PAD. Ultraviolet–Visible spectroscopy results and digital image analysis revealed that the fabricated sensor can detect CN− with concentration down to 1.0 ppm. The colorimetric response was also obtained for real water samples spiked with CN−. The results stipulated in this work offer baseline information that can be used in developing highly selective and sensitive digital sensing devices for affordable; accessible; and fast water contaminant monitoring and other related applications.